2019
DOI: 10.1038/s41431-019-0366-9
|View full text |Cite
|
Sign up to set email alerts
|

De novo variants in HK1 associated with neurodevelopmental abnormalities and visual impairment

Abstract: Hexokinase 1 (HK1) phosphorylates glucose to glucose-6-phosphate, the first rate-limiting step in glycolysis. Homozygous and heterozygous variants in HK1 have been shown to cause autosomal recessive non-spherocytic hemolytic anemia, autosomal recessive Russe type hereditary motor and sensory neuropathy, and autosomal dominant retinitis pigmentosa (adRP). We report seven patients from six unrelated families with a neurodevelopmental disorder associated with developmental delay, intellectual disability, structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 51 publications
1
20
1
Order By: Relevance
“…None of the patients with the E847K mutation had optic disc atrophy. There is also a report describing patients with syndromic RP and/or optic atrophy caused by Gly414Glu, Ser445Leu, and Thr457Met mutations in the HK1 gene (14). From these earlier findings and our data, we conclude that patients Figures 8E and 8 F. Cone density of patient II-3 are not countable throughout 2 to 5 degrees.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…None of the patients with the E847K mutation had optic disc atrophy. There is also a report describing patients with syndromic RP and/or optic atrophy caused by Gly414Glu, Ser445Leu, and Thr457Met mutations in the HK1 gene (14). From these earlier findings and our data, we conclude that patients Figures 8E and 8 F. Cone density of patient II-3 are not countable throughout 2 to 5 degrees.…”
Section: Discussionsupporting
confidence: 79%
“…Later, several groups reported similar non-syndromic autosomal dominant retinitis pigmentosa or allied diseases with the same heterozygous E847K mutation in the HK1 gene (10)(11)(12)(13). Most recently, seven patients from six unrelated families with NEDVIBA were reported by Okur et al They identified four different de novo heterozygous missense mutations in the HK1 gene in these patients (14). They also reported that these patients were syndromic, and several cases had a combination of retinitis pigmentosa and optic atrophy.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…12c ) that were critical specifiers for different germ layers. For example, neurodevelopmental genes (such as HK1 28 , VWC2 29 , and NECTIN1 30 ) , a metabolic gene (FOXA3) 31 , and genes in involved in cardiovascular differentiation ( TMEM88 32 and VIM 33 ) were highly expressed in tissues derived from ectoderm (i.e., cerebrum, cerebellum, and retina), endoderm (i.e., liver, small intestine, colon, and stomach), and mesoderm (typically, heart), respectively (Supplementary Fig. 12d ).…”
Section: Resultsmentioning
confidence: 99%
“…However, heterozygous de novo missense mutations in the same gene detected recently in six patients with developmental delay, intellectual disability, structural brain abnormality and visual impairment, were associated with normal hexokinase activity. 31 …”
Section: Discussionmentioning
confidence: 99%